The Senso Question Answering approach to Portuguese QA@CLEF-2007 - Saias, José (2009)
This article has the Working Notes about the Universidade de Évora's participation in QA@CLEF2007 (http://www.clef-campaign.org/), based on the Senso question answer system and the Portuguese monolingual task.